Access to graduate education in Brazil: Predictors of choice and enrollment in master’s degree programs - Colombo,Daniel Gama e (2021)
Abstract This paper assesses the factors associated with access to master’s degree programs in Brazil, investigating potential evidence of inequity. The main findings are: (a) students are more likely to choose a master’s degree program in the same university or close to where they graduated from college; (b) academic performance and activities during college are associated with an increase in the relative odds of progressing to graduate education; (c) male students and those with a higher household income are more likely to start a master’s program; and (d) for most broad academic fields, no evidence that nonwhite students are less likely to start a master’s program is found.